Small states and regional stability in South Asia - Kabir, Humayun; Bangladesh Institute of International and Strategic Studies (Dhaka : The University Press, 2005)
Contributed articles on political conditions in South Asia presented and discussed in many workshops and seminars
'Bangladesh Institute of International and Strategic Studies'
Includes bibliographical references and index
Keywords: States, Small -- Congresses; South Asia -- Politics and government -- Congresses